The Effectiveness of Mindfulness-Based Eating Awareness Training (MB-EAT) on Perceived Stress and Body Mass Index in Overweight Women - Oraki, Mohammad; Ghorbani, Mahsa (International Journal of Applied Behavioral Sciences, 2019)
Introduction: Being overweight is a serious threat to women’s health, imposing enormous costs on the individual, national and global levels. The purpose of this study was to evaluate the effectiveness of mindfulness-based eating awareness training on perceived stress and body mass index in overweight women in Tehran. Methods: The research design is experimental with pre-posttest and control group. The statistical population consisted of all women referring to health center in Niavaran, Tehran in the first trimester of 2019 due to being overweight. They were replaced randomly. Mindfulness group training was conducted in 8 sessions once a week. Before and after the intervention, participants completed a perceived stress scale and their BMI was calculated. Results: Results of covariance analysis showed that mindfulness training significantly decreased perceived stress (p<0.05) and also significantly decreased body mass index in the experimental group compared to the control group (p<0.05). Conclusion: Given these findings, it can be said that in addition to the usual therapeutic treatments for overweight, psychological training for women can play an effective role in their health beliefs and behaviors. Declaration of Interest: None Key words: Perceived stress, Mindfulness approach, Overweight women.